1998
DOI: 10.1002/(sici)1097-0177(199812)213:4<412::aid-aja6>3.3.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic expression of tropomyosin promotes myofibrillogenesis in mutant axolotl hearts

Abstract: Expression of tropomyosin protein, an essential component of the thin filament, has been found to be drastically reduced in cardiac mutant hearts of the Mexican axolotl (Ambystoma mexicanum) with no formation of sarcomeric myofibrils. Therefore, this naturally occurring cardiac mutation is an appropriate model to examine the effects of delivering tropomyosin protein or tropomyosin cDNA into the deficient tissue. In this study, we describe the replacement of tropomyosin by using a cationic liposome transfection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 0 publications
3
23
0
Order By: Relevance
“…Similar observations demonstrating essential functions for troponins in sarcomere formation, as well as exacerbation of defects by unregulated actomyosin activity during myofibril assembly, have been made in studies of zebrafish striated muscles (Sehnert et al, 2002;Huang et al, 2009;Ferrante et al, 2011). The primary direct evidence for a role of TM in myofibril assembly comes from the Mexican axolotl, in which the naturally occurring cardiac mutation eliminates TM expression and disrupts cardiac myofibril assembly via aberrant intracellular targeting of a host of thin filament and sarcomere-associated proteins and lack of coalescence of organized sarcomeres (Lemanski, 1973;Lemanski, 1979;Lemanski et al, 1980;Fuldner et al, 1984;Starr et al, 1989;Erginel-Unaltuna and Lemanski, 1994;La France and Lemanski, 1994;Zajdel et al, 1998;Zajdel et al, 1999;McLean et al, 2006;Zajdel et al, 2007). A heart-specific TM isoform (tpm4) is also essential for myofibril assembly and heartbeat in zebrafish (Zhao et al, 2008), but the lack of confirmed association of tpm4 with thin filaments makes it unclear whether the myofibril assembly defects observed in tpm4-deficient zebrafish represent primary or indirect events.…”
Section: Introductionsupporting
confidence: 57%
“…Similar observations demonstrating essential functions for troponins in sarcomere formation, as well as exacerbation of defects by unregulated actomyosin activity during myofibril assembly, have been made in studies of zebrafish striated muscles (Sehnert et al, 2002;Huang et al, 2009;Ferrante et al, 2011). The primary direct evidence for a role of TM in myofibril assembly comes from the Mexican axolotl, in which the naturally occurring cardiac mutation eliminates TM expression and disrupts cardiac myofibril assembly via aberrant intracellular targeting of a host of thin filament and sarcomere-associated proteins and lack of coalescence of organized sarcomeres (Lemanski, 1973;Lemanski, 1979;Lemanski et al, 1980;Fuldner et al, 1984;Starr et al, 1989;Erginel-Unaltuna and Lemanski, 1994;La France and Lemanski, 1994;Zajdel et al, 1998;Zajdel et al, 1999;McLean et al, 2006;Zajdel et al, 2007). A heart-specific TM isoform (tpm4) is also essential for myofibril assembly and heartbeat in zebrafish (Zhao et al, 2008), but the lack of confirmed association of tpm4 with thin filaments makes it unclear whether the myofibril assembly defects observed in tpm4-deficient zebrafish represent primary or indirect events.…”
Section: Introductionsupporting
confidence: 57%
“…Their studies using the peptide model system also show that a peptide from human cTnT, hcTn70-170, promotes the affinity of striated muscle tropomyosin for actin up to 15 folds [Palm et al, 2003]. Tropomyosin expression has been shown before to be dramatically decreased in the gene c mutant animals [LaFrance and Zajdel et al, 1998;Zhang et al, 2003]. Decreased expression of cTnT protein in the mutant hearts could possibly be the reason for the failure of incorporation of tropomyosin protein to the myofibril structure, thus abnormally high degradation of tropomyosin protein in the mutant hearts may occur.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, myocytes from the different regions could be under different transcriptional or translational control. Interestingly, it has been reported that the mutant conus region also contains significant amounts of tropomyosin although the ventricular areas are virtually devoid of this protein [Zajdel et al, 1998]. Very likely, cTnT isoforms are partially regulated by common factors shared with tropomyosin, which influences their expression or RNA processing in the mutant condition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Actin and tropomyosin are essential components of the thin filaments. 8,9 Alpha-actinin is an actin-binding protein and one of the major structural elements of the Z-disc, interacting with tropomyosin. 10 All of these proteins are mutually bound as a complex and reduced expression of one of them causes instability or degradation of the others.…”
Section: © 2 0 0 9 L a N D E S B I O S C I E N C E D O N O T D I S mentioning
confidence: 99%